TEOLOGI ISLAM KONTEKSTUAL- TRANSFORMATIF - Said, Nur (FIKRAH, 2013)
A Religion has strong influence on humanity, morality, ethics, and aesthetics in the process of humankind development. This of course, will construct the worldview individually and socially as well. It may be said that nearly all the social life haven’t been ignored the role of religion in the making humanity as an expression of the whole of collective life. Therefore the religious spirit is also in constant change, which formulated in a certain theology in line with the historical progress contextually. In addition, theology is a discourse through which believers develop and express the content of their faith as they have confessed it. The notion of this article tries to elaborate the contextualization of Islamic Theology in Indonesia in respecting to the social phenomena such as colonialism, oppression, human right, and pluralism in Indonesia. It also gives paradigmatic contribution to interpret the Secret text on historical situation in order to determine public morality more than just individual morality. The main points are a searching of meaning between “text” and context in Indonesia society as manifestation of Islamic contextual theology. It means that Islam should be “translated” in particular way in order may “come down to earth” and meet in the contemporary demands. Keywords: Islam, contextual-transformative theology, human right, Indonesia